2013
DOI: 10.1038/ncb2827
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-205 controls neonatal expansion of skin stem cells by modulating the PI(3)K pathway

Abstract: Skin stem cells (SCs) are specified and rapidly expanded to fuel body growth during early development. However, molecular mechanisms that govern the amplification of skin SCs remain unclear. Here we report an essential role for miR-205, one of the most highly expressed miRNAs in skin SCs, in promoting neonatal expansion of these cells. Unlike most mammalian miRNAs, genetic deletion of miR-205 causes neonatal lethality with severely compromised epidermal and hair follicle growth. In the miR-205 KO skin SCs, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 47 publications
13
140
0
Order By: Relevance
“…To additionally purify the precursors of future bulge SCs from within the ORS compartment of same stage growing HFs (HFSC), we used a GFP reporter line for the SC marker Sox9 crossed with an RFP reporter for all skin epithelial cells under the K14 promoter (Figure 1C), as previously described (Wang et al, 2013). From K14-RFP;Sox9-GFP transgenic P5 back skins we prepared single cells, stained for basement membrane marker ITGA6 and sorted by FACS the HFSCs as the RFP High ITGA6 High GFP + population.…”
Section: Resultsmentioning
confidence: 99%
“…To additionally purify the precursors of future bulge SCs from within the ORS compartment of same stage growing HFs (HFSC), we used a GFP reporter line for the SC marker Sox9 crossed with an RFP reporter for all skin epithelial cells under the K14 promoter (Figure 1C), as previously described (Wang et al, 2013). From K14-RFP;Sox9-GFP transgenic P5 back skins we prepared single cells, stained for basement membrane marker ITGA6 and sorted by FACS the HFSCs as the RFP High ITGA6 High GFP + population.…”
Section: Resultsmentioning
confidence: 99%
“…miR-205 was also found to target and suppress ErbB3 and VEGF-A in tumor tissues (55); to promote apoptosis by targeting the HER3 receptor (56); and to increase cellular proliferation in prostate cancer by targeting the tumor suppressors, PTEN and SHIP2 (32). In a recent study, of genetic deletion of miR-205, Wang and colleagues found that the loss of miR-205 led to neonatal lethality and demonstrated a network of negative regulators of the PI(3)K pathway were directly targeted by miR-205 (34). All of the studies described above reveal the importance of miR-205; however, no report has offered a rigorous proteomics identification of the targets of miR-205 with diverse functions and properties.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we explored urothelial miRNA expression profiles and revealed that expression of miR-205 in a differentiation stage-specific manner in urothelium. Although several studies have elucidated that targets of miR-205 can modulate a wide spectrum of pathways in many cell types, including Akt signaling (31), PTEN (32), EMT program (33), and PI(3)K pathway (34). However, no study has systematically examined the role of miR-205 in normal urothelial differentiation.…”
mentioning
confidence: 99%
“…For example, in mice, deletion of miR-128 results in fatal epilepsy due de-repression of several components of the MAPK pathway, leading to a significant increase in ERK2 phosphorylation [52]. Similarly, loss of miR-205 results in neonatal lethality in mice with compromised epidermal and hair follicle growth [53], presumably by modulating the expression of multiple components of the PI(3)K signaling pathway. Finally, a recent study has implicated Drosophila's miR-iab-8 in CNV patterning and fly fertility through the regulation of genes whose products act together within a protein complex [54].…”
Section: Endogenous Mirnas Exert Mild Repression On Many Targetsmentioning
confidence: 99%